Geochemical Assessment of Limestone for Cement Manufacturing. (2016) - Bouazza, Noureddine; Mrihi, Abdelaziz El; Maâte, Ali
Abstract: The El Mashar Unit of Triassic-Quaternary successions from limestone deposit of Cement Lafarge quarry (North, Morocco) is characterized by the occurrence of several sedimentary rocks. This study, based on chemical composition of more than 1600 samples of drill cuttings provides insight into the chemical parameters controlling the use of limestone in cement making. El Mashar formation can subdivided into twelve facies based on the chemical composition and geological position of different lithostratigraphic successions, being: dolomite Triassic limestone, Rhaetian limestone marl, Hettangian nodular limestone, Hettangian limestone with low magnesium, Hettangian limestone with silica, Hettangian limestone with high magnesium, Sinemurian brecciated limestone, basal Sinemurian limestone, central Sinemurian limestone, sommital Sinemurian limestone, Eocene marl and Quaternary topsoil. This study documents the importance of geochemical assessment of limestone for cement manufacturing.